The efficacy and safety of continued hydroxycarbamide therapy versus switching to ruxolitinib in patients with polycythaemia vera: a randomized, double‐blind, double‐dummy, symptom study (RELIEF). (8th November 2016) - Mesa, Ruben; Vannucchi, Alessandro M.; Yacoub, Abdulraheem; Zachee, Pierre; Garg, Mamta; Lyons, Roger; Koschmieder, Steffen; Rinaldi, Ciro; Byrne, Jennifer; Hasan, Yasmin; Passamonti, Francesco; Verstovsek, Srdan; et al.
Summary: The randomized, double‐blind, double‐dummy, phase 3b RELIEF trial evaluated polycythaemia vera (PV)‐related symptoms in patients who were well controlled with a stable dose of hydroxycarbamide (also termed hydroxyurea) but reported PV‐related symptoms. Patients were randomized 1:1 to ruxolitinib 10 mg BID ( n  = 54) or hydroxycarbamide (prerandomization dose/schedule; n  = 56); crossover to ruxolitinib was permitted after Week 16. The primary endpoint, ≥50% improvement from baseline in myeloproliferative neoplasm ‐symptom assessment form total symptom score cytokine symptom cluster (TSS‐C; sum of tiredness, itching, muscle aches, night sweats, and sweats while awake) at Week 16, was achieved by 43·4% vs. 29·6% of ruxolitinib‐ and hydroxycarbamide‐treated patients, respectively (odds ratio, 1·82; 95% confidence interval, 0·82–4·04; P  =   0·139). The primary endpoint was achieved by 34% of a subgroup who maintained their hydroxycarbamide dose from baseline to Weeks 13–16. In a post hoc analysis, the primary endpoint was achieved by more patients with stable screening‐to‐baseline TSS‐C scores (ratio ≤ 2) receiving ruxolitinib than hydroxycarbamide (47·4% vs. 25·0%; P  =   0·0346). Ruxolitinib treatment after unblinding was associated with continued symptom score improvements. Adverse events were primarily grades 1/2 with no unexpected safety signals. Ruxolitinib was associated with a nonsignificant trend towards improved PV‐related symptoms versus hydroxycarbamide, although an unexpectedly large proportion of patients who maintained their hydroxycarbamide dose reported symptom improvement.